2005
DOI: 10.1007/s00520-005-0886-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in terminal care—with special reference to age, gender and marital status

Abstract: Young and married patients may be at higher risk for perceived low quality of life at the end of life. EORTC QLQ-C30 could be used as a clinical tool for screening of symptoms and reduced functioning in palliative care, but may not be appropriate for use in the most severely ill patients. Limitations of the instrument and the need for robust measurements of patient mix are discussed. Proxy ratings of physical symptoms and nurse responsibility to include QoL assessment in daily practice would increase attrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
79
3
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 58 publications
17
79
3
5
Order By: Relevance
“…The levels of impairment and symptoms found are consistent with those from other studies on cancer patients at the end of life [29,32]. However, most previous studies were either cross-sectional studies, in which the patients were followed for a short period of time, or they presented longitudinal data from cohorts of patients varying at subsequent assessments due to drop-out or death [20,21,32]. Adequate comparisons are therefore difficult, and to our knowledge, this is one of the first studies describing how a large number of cancer patients perceive their HRQL over time at the end of life.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The levels of impairment and symptoms found are consistent with those from other studies on cancer patients at the end of life [29,32]. However, most previous studies were either cross-sectional studies, in which the patients were followed for a short period of time, or they presented longitudinal data from cohorts of patients varying at subsequent assessments due to drop-out or death [20,21,32]. Adequate comparisons are therefore difficult, and to our knowledge, this is one of the first studies describing how a large number of cancer patients perceive their HRQL over time at the end of life.…”
Section: Discussionsupporting
confidence: 80%
“…The golden standard for subjective outcome assessment is self-reporting, but compliance in completing HRQL questionnaires is known to fall considerably as death approaches [9]. Most existing studies have therefore been subject to serious attrition, meaning that a rapidly decreasing number of patients have been able to complete the later assessments [15,21,32]. Thus, the changes in HRQL and symptoms identified at the group level may merely reflect a diminishing and varying study sample.…”
Section: Introductionmentioning
confidence: 98%
“…7,8 Sociodemographic variables that predict QoL in the general population 35 colleagues found that being married was associated with lower QoL, while Jordhoy and colleagues found no influence from a live-in partner. 8,36 In line with our findings, it seems that the overall influence of sociodemographic characteristics on QoL amongst severely diseased patients is superseded by their disease status. 8 To avoid artificially conflating the relationship between depression severity and QoL, we used a modified depression measure that included only the emotional and cognitive symptoms of depression.…”
Section: Discussionsupporting
confidence: 89%
“…Within a year, fatigue is observed in approximately one million patients in Europe [1]. It affects from 25% to 100% patients in every stage of cancer [2][3][4][5][6][7][8][9][10][11]. However, it is more frequent in the far advanced stage of cancer (90-100%) [5][6][7], and its intensity escalates with the progression of the disease [6].…”
Section: Introductionmentioning
confidence: 99%